Digital Cultural Production In The Entertainment Program "Tembang Pantura" on Cirebon Local Television - Cusniawati Cusniawati; Siti Sarah Shafira; Venita Octavia; Khaerudin Imawan; Dedet Erawati (Asian Journal of Social and Humanities, 2024)
This research examines the digital cultural production in the entertainment program "Tembang Pantura" on local television in Cirebon, Indonesia. The study explores how the program preserves local cultural heritage while adapting to contemporary digital entertainment trends. A descriptive qualitative method was used, with data collected through interviews and observations of the production team, local artists, and the audience. The research focuses on how "Tembang Pantura" integrates traditional Cirebon elements such as the local language and tarling music with modern digital production techniques. The findings show that "Tembang Pantura" successfully preserves and promotes Cirebon's cultural heritage while appealing to a wide audience. The use of modern technology enhances the program’s accessibility and relevance in today’s media landscape. Moreover, the program fosters cultural identity by continuously adapting to technological advancements and audience preferences. In conclusion, "Tembang Pantura" serves as an important platform for promoting local culture through digital media, demonstrating how regional television programs can sustain cultural relevance in the digital era.